How Technology Affects Behavioral Intention (Case Study of Online Transportation in Indonesia and Thailand) - Munandar, Jono M.; Munthe, Ribka Cynthia F. (The South East Asian Journal of Management, 2019)
Research Aims: Using two countries as the object, this study aims to analyze the influence of technology readiness towards favorableness on online transportation consumers in Indonesia and Thailand. Design/methodology/approach: Empirical evidence for the research was derived from a survey that collected data from 500 students in Indonesia and Thailand, analyzed using Logit Biner method with the help of software SPSS. Research Findings: The result of this study shows that there were two hypotheses accepted, H1 (optimism influences favorableness) and H3 (insecurity has an effect on favorableness), while other hypotheses (H2 and H4) are not significant. Theoretical Contribution/Originality: This study analyzes the influence of technology readiness to favorableness in two countries in South East Asia, Indonesia and Thailand, focusing on online transportation. Managerial Implication in the South East Asian context: The result can be useful for online transportation companies in South East Asian Research limitation & implications: This study was limited by subject and sample